2016
DOI: 10.1016/j.bmcl.2016.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological evaluation of mono-arylimidamides as antileishmanial agents

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Synthesis of the indole-bichalcophene diamidine derivatives 4a-d is outlined in Scheme 1 . The bis-nitriles 3a-d were prepared by Stille coupling [11] , [12] , [13] reaction between the bromo derivatives 1a-d and 2-(trimethylstannyl)-1-( tert -butoxycarbonyl)- 1 H -indole-6-carbonitrile 2 using palladium tetrakistriphenylphosphine as a catalyst. The bis-nitriles 3a-d on reaction with a THF solution of lithium bis(trimethylsilyl)amide [14] , followed by treatment with ethanolic HCl yielded the hydrochloride salts of the diamidines 4a-d .…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the indole-bichalcophene diamidine derivatives 4a-d is outlined in Scheme 1 . The bis-nitriles 3a-d were prepared by Stille coupling [11] , [12] , [13] reaction between the bromo derivatives 1a-d and 2-(trimethylstannyl)-1-( tert -butoxycarbonyl)- 1 H -indole-6-carbonitrile 2 using palladium tetrakistriphenylphosphine as a catalyst. The bis-nitriles 3a-d on reaction with a THF solution of lithium bis(trimethylsilyl)amide [14] , followed by treatment with ethanolic HCl yielded the hydrochloride salts of the diamidines 4a-d .…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Zhu et al (2016), 18 compounds containing a single terminal group of pyridylimidamide (mono‐AIAs) were synthetized and evaluated for their antileishmanial potential in relation to standard drugs. Only three compounds showed good efficacy and low toxicity, in which Compound 1b had IC 50 of 310 nM, Compound 1k with IC 50 140 nM and Compound 1d with IC 50 340 nM, compared to AmB with IC 50 40 nM.…”
Section: Resultsmentioning
confidence: 99%
“…Among a series of carboline derivatives reported by Manda et al [98], compounds 25a (IC 50 = 12.7 µM) and 25b (IC 50 = 9.1 µM), which are derivatives of the commercially available tetrahydro-β-carboline prepared in a single procedure were the best candidates against L. donovani (promastigotes). Zhu et al [99] reported compounds 26a and 26b , which are derived from arylamidamide using the reaction between amino diarylfurans and 2-pyridyl thioimidate analogs, as the most active antileishmanial agents against both intracellular L. donovani and L. amazonensis amastigotes, with IC 50 values ranging from 0.13 to 0.31 µM. A series of 4-alkapolyenylpyrrolo[1,2-a]quinoxaline derivatives, including compounds 27a and 27b , which exhibited remarkable inhibitory potential against two Leishmania spp.…”
Section: Recent Progress Of Antiprotozoan Agentsmentioning
confidence: 99%